2010
DOI: 10.1080/01449291003752914
|View full text |Cite
|
Sign up to set email alerts
|

Trust in medical technology by patients and healthcare providers in obstetric work systems

Abstract: Multiple types of users (i.e. patients and care providers) have experiences with the same technologies in health care environments and may have different processes for developing trust in those technologies. The objective of this study was to assess how patients and care providers make decisions about the trustworthiness of mutually used medical technology in an obstetric work system. Using a grounded theory methodology, we conducted semi-structured interviews with 25 patients who had recently given birth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Trust is a concept that has been proposed from several theoretical streams; research of trust in healthcare work has identified two antecedents: interpersonal trust between patients and physicians [2,19,29,41] and patient's trust in health systems [3,47]. Montague, et al [28] used a qualitative method to identify that patient-provider trust relationships mediate how trust is developed in medical technologies, and influence how the technology is used in care-providing activities.…”
Section: Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust is a concept that has been proposed from several theoretical streams; research of trust in healthcare work has identified two antecedents: interpersonal trust between patients and physicians [2,19,29,41] and patient's trust in health systems [3,47]. Montague, et al [28] used a qualitative method to identify that patient-provider trust relationships mediate how trust is developed in medical technologies, and influence how the technology is used in care-providing activities.…”
Section: Trustmentioning
confidence: 99%
“…Trusting care providers is the largest and most salient component of the trust in technology coding scheme [28]. Tele-healthcare service offers another channel to fulfill customers' need on holistic wellness.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Johnsons (2007) demonstrated that trust in online banking technology is a critical mediator in getting consumers to increase their transaction frequency and value from online banking. Healthcare researchers find that technology characteristics and trust in care providers influence patient trust in technology (Montague, Winchester III, & Kleiner, 2010). Some have even argued that there is a tendency for individuals such as critical care nurse and airline pilots to place inappropriate levels of trust in technology, leading to complacency and adverse consequences (Browne & Cook, 2011).…”
Section: Trust In Technologymentioning
confidence: 99%
“…Consequently, expected reliability can be seen as a pre-condition for building user-trust [16]. Some former studies already described the relationship between reliability of technologies and their consequences in different ways.…”
Section: Introductionmentioning
confidence: 99%